ALIRAN-ALIRAN FILSAFAT PENDIDIKAN (KLASIK DAN MODERN) DALAM PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - Iswantir Muhamad (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2017)
The philosophy of Islamic education is an attempt to search for concepts that direct human beings among the various symptoms of various educational processes in a holistic and comprehensive design based on Islamic principles. The source and values of education in the view of Islamic education philosophy is derived from Allah SWT, so that all sources and values developed in the school of classical and modern education are very much different from the development of Islamic education philosophy. The development of human aspects in the view of the schools of philosophy classical and modern education only touches on certain aspects, whereas in the view of Islamic education philosophy should refer to all aspects of human nature in Islam Filsafat pendidikan Islam adalah usaha untuk mencari konsep-konsep yang mengarahkan manusia diantara berbagai gejala yang bermacam-macam proses pendidikan dalam rancangan yang berpadu dan menyeluruh berdasarkan prinsip-prinsip Islam. Sumber dan nilai-nilai pendidikan dalam pandangan filsafat pendidikan Islam adalah berasal dari Allah Swt, sehingga semua sumber dan nilai yang dikembangkan dalam aliran pendidikan klasik dan modern sangat jauh berbeda dengan pengembangan filsafat pendidikan Islam.Pengembangan aspek-aspek kemanusiaan dalam pandangan aliran-aliran filsafat pendidikan klasik dan modern hanya menyentuh beberapa aspek tertentu, sedangkan dalam pandangan filsafat pendidikan Islam harus mengacu ke semua aspek hakikat manusia dalam Islam.